Memory suppression is an active process that improves over childhood - Paz-Alonso, Pedro M.; Ghetti, Simona; Matlen, Bryan J.; Anderson, Michael C.; Bunge, Silvia A. (Frontiers in Human Neuroscience, 2009)
We all have memories that we prefer not to think about. The ability to suppress retrieval of unwanted memories has been documented in behavioral and neuroimaging research using the Think/No-Think (TNT) paradigm with adults. Attempts to stop memory retrieval are associated with increased activation of lateral prefrontal cortex (PFC) and concomitant reduced activation in medial temporal lobe (MTL) structures. However, the extent to which children have the ability to actively suppress their memories is unknown. This study investigated memory suppression in middle childhood using the TNT paradigm. Forty children aged 8 to 12 and 30 young adults were instructed either to remember (Think) or suppress (No-Think) the memory of the second word of previously studied word-pairs, when presented with the first member as a reminder. They then performed two different cued recall tasks, testing their memory for the second word in each pair after the Think/No-Think phase using the same first studied word within the pair as a cue (intra-list cue) and also an independent cue (extra-list cue). Children exhibited age-related improvements in memory suppression from age 8 to 12 in both memory tests, against a backdrop of overall improvements in declarative memory over this age range. These findings suggest that memory suppression is an active process that develops during late childhood, likely due to an age-related refinement in the ability to engage PFC to down-regulate activity in areas involved in episodic retrieval.